2014
DOI: 10.1111/hpb.12280
|View full text |Cite
|
Sign up to set email alerts
|

Determinants and outcomes of adherence to recommendations from a multidisciplinary tumour conference for hepatocellular carcinoma

Abstract: There are patient-related as well as physician-related reasons for non-adherence to recommendations. Non-adherence affects clinical outcomes and can be avoided in selected cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 19 publications
(18 reference statements)
3
12
0
Order By: Relevance
“…Our data is in line with previous studies which showed improved survival by MDT management [1824]. The strength of this data is the relatively large sample size that enabled us to create exactly matched cohort.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our data is in line with previous studies which showed improved survival by MDT management [1824]. The strength of this data is the relatively large sample size that enabled us to create exactly matched cohort.…”
Section: Discussionsupporting
confidence: 89%
“…However, MDT with participation by experts from multiple academic disciplines requires additional medical resources and time per patient, which leads to significant healthcare burden and high cost [17]. Several previous studies suggested that MDT management for HCC may improve survival [1824], yet is limited by analyzing small number of patients [1822], comparing patients who were treated in different time period [18,19,22], including those only received MDT management [20,21,23,24], or including those who received curative treatment only [20]. Recently, Serper et al, reported that MDT management was associated with reduced mortality, by analyzing 3,988 patients who received care through the Veterans Administration in involving 128 centers in U.S. [25].…”
Section: Introductionmentioning
confidence: 99%
“…The promissory tenor of genomic testing is reflected in our findings that treating physicians perceived the clinical utility of genomic testing to be significant for few patients but low for most patients, which was further evidenced through the low uptake of MGTB recommendations related to genomic testing by patients whose cases were reviewed. While these findings are consistent with previous research on follow up on tumor board recommendations [15, 19, 20], our study cannot explain the specific factors that contributed to uptake of MGTB recommendations by physicians and patients.…”
Section: Discussionsupporting
confidence: 88%
“…Research suggests that multidisciplinary cancer care teams can improve patients’ therapy planning, pain control, and medication adherence, though findings supporting their effectiveness in impacting patient survival and the costs of care are limited [16–18]. This may be due in part to discordance between recommendations and patient values and lack of follow up on tumor board recommendations [19, 20]. Nevertheless, studies suggest that multidisciplinary tumor boards and the use of standardized templates in tumor board conferences can improve oncology patient outcomes based on proxy measures such as the adherence to standards of care and national guidelines for treatment [21, 22].…”
Section: Introductionmentioning
confidence: 99%
“…It is important to note that the correct functioning of the MDT meeting relies on the proper union between the scientific evidence and the local experience in the diagnosis and cure of a given hepatobiliary disease. A MDT well balanced among specialties represented, and authoritative in all its specialists, provides better patient management resulting in better short-and long-term outcomes (56)(57)(58)(59).…”
Section: Minimum Hospital Requirements In Hepatobiliary Surgerymentioning
confidence: 99%